Correlation of Height and Arm Muscle Strength o Volleyball Serving Ability of Health Vocational School Students - Muhammad Sukron Fauzi; Didik Cahyono; Paryadi Paryadi; Gyta Krisdiana Cahyaningrum; Naheria Naheria; Nurjamal Nurjamal; Muhammad Saiin (Indonesian Journal of Innovation Multidisipliner Research, 2024)
This study aims to determine the relationship between height and arm muscle strength to volleyball serving ability by health vocational school students. This study is quantitative descriptive which tries to describe the serving ability of students volleyball in relation to height and arm muscle strength. The population of this study is all students of SMK Kesehatan Samarinda, while sampling uses purposive sampling techniques. The data collection technique uses a height test with measurements, an arm muscle strength test with a medicine ball test, and a volleyball service ability test. The data analysis technique uses descriptive analysis and inferential analysis. This analysis uses the SPSS 20.0 program using a multiple linear regression test with a significant level of α = 5%. Based on the data analysis conducted in this study, the conclusions were obtained. 1) there is a relationship between height and upper serve ability in volleyball with r count (r0) = 0.445(P<0.05), 2) there is a relationship between arm muscle strength and upper serve ability in volleyball with r count (r0) = 0.635 (P<0.05), 3). There is a relationship between height and arm muscle strength together with the ability to serve the top in volleyball, there is a result of R calculation (R0) = 0.798 (P<0.05). From the results of the study, height and arm muscle strength are known to be related to the ability to serve the top in volleyball, in general, it can be drawn a straight line that students who have height and arm muscle strength can show better serving ability over volleyball.